Gas barrier laminate and gas barrier seal paper
Patent Information
- Application Number
- JP2021063036
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-01
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-04-01
Smart Images

Figure 0007643145000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a gas barrier laminate and a gas barrier seal paper using the same. [Background technology]
[0002] Conventionally, packaging materials that use paper as a base material and have water vapor barrier properties and gas barrier properties (particularly oxygen barrier properties) have been known. Such packaging materials are used in packaging foods, medical products, electronic components, etc., to prevent deterioration of the contents.
[0003] A common method for imparting water vapor barrier properties or gas barrier properties to a paper substrate is to laminate a synthetic resin film or metal foil with excellent gas barrier properties onto the paper substrate. However, materials in which a synthetic resin film or metal foil is laminated onto a paper substrate have problems in terms of the environment, since it is difficult to recycle the paper or synthetic resin after use.
[0004] Therefore, gas barrier materials using paper as a base material without using synthetic resin films or the like have been developed. For example, Patent Documents 1 and 2 disclose paper barrier materials in which a water vapor barrier layer and a gas barrier layer are provided in this order on a paper base material. In Patent Document 1, the water vapor barrier layer contains a water vapor barrier resin and a water repellent, and the gas barrier layer contains a water-soluble polymer and a surfactant. In Patent Document 2, it is disclosed that the water vapor barrier layer and the gas barrier layer have a water-soluble polymer or a water-suspendable polymer. The binder resin of the gas barrier layer in Patent Document 2 is a polyvinyl alcohol resin.
[0005] Furthermore, in Patent Document 3, the basis weight is 25 g / m 2 More than 400g / m 2 The following paper barrier material is disclosed, which has a paper barrier base paper having a water vapor barrier layer and a gas barrier layer containing a water-soluble polymer on a paper substrate, and further has a protective layer on at least one side of the paper barrier base paper. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2017 / 170462 [Patent Document 2] International Publication No. 2013 / 069788 [Patent Document 3] JP 2018-058360 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described above, a gas barrier laminate in which a water vapor barrier layer and a gas barrier layer are provided in this order on a paper substrate is known, and the gas barrier layer contains polyvinyl alcohol as a water-soluble polymer. However, the inventors have found through their studies that when a gas barrier layer containing polyvinyl alcohol is laminated on a paper substrate, the water resistance is low, and the gas barrier property may be reduced by applying a sealant using an aqueous medium (for example, coating of an aqueous heat sealant).
[0008] The present disclosure relates to a gas barrier laminate that has good water resistance, water vapor barrier property, and gas barrier property, and further, can exhibit sufficient gas barrier property (particularly gas barrier property in a high humidity environment) even after applying a sealant using an aqueous medium.The present disclosure also relates to a gas barrier seal paper using such a gas barrier laminate. [Means for solving the problem]
[0009] As a result of intensive research by the present inventors, it was found that the wetting tension, water absorption, and gas barrier strength of the gas barrier layer surface were It has been found that the above problems can be solved by adjusting the acidity to a predetermined range.
[0010] That is, the present disclosure provides the following <1> ~ <15> Regarding. <1> A gas barrier laminate having a water vapor barrier layer and a gas barrier layer in this order on at least one surface of a paper substrate, the gas barrier layer contains a water-suspendable polymer, the wetting tension of the surface of the gas barrier layer measured in accordance with JIS K 6768:1999 is 60 mN / m or more and 70 mN / m or less; The Cobb water absorption of the surface of the gas barrier layer, measured in accordance with JIS P 8140:1998 at a temperature of 23°C and a contact time of 120 seconds, is 2.5 g / m 2 is as follows: When a laminate sheet is formed by laminating a 20 μm-thick non-oriented polypropylene film to the surface of the gas barrier layer of the gas barrier laminate, the oxygen permeability of the laminate sheet measured at a temperature of 23° C. and a relative humidity of 85% in accordance with JIS K 7126-2:2006 is 20 mL / m 2 A gas barrier laminate having a gas barrier resistance of 1000 psi or less per day atm.
[0011] <2> The water-suspendable polymer contains at least one selected from the group consisting of a urethane-based resin and a vinylidene chloride-based resin. <1> 2. The gas barrier laminate according to claim 1 . <3> The urethane resin has an oxygen permeability of 100.0 mL / m at 23° C. and 50% RH when converted into a 25 μm thick sheet. 2 ·day·atm or less, <2> 2. The gas barrier laminate according to claim 1 . <4> The gas barrier layer contains a layered inorganic compound. <1> ~ <3> 13. The gas barrier laminate according to claim 12, <5> the aspect ratio of the layered inorganic compound contained in the gas barrier layer is 200 or more and the thickness is 100 nm or less; <4> 2. The gas barrier laminate according to claim 1 . <6> The layered inorganic compound contained in the gas barrier layer is at least one selected from the group consisting of mica, bentonite, and kaolin. <4> or <5> 2. The gas barrier laminate according to claim 1 . <7> the layered inorganic compound contained in the gas barrier layer is a layered inorganic compound B having an aspect ratio of 500 or more, The gas barrier layer further comprises a layered inorganic compound A having an aspect ratio of less than 500. <4> ~ <6> 13. The gas barrier laminate according to claim 12,
[0012] <8> The water vapor barrier layer comprises a layered inorganic compound, a cationic resin, and an anionic binder. <1> ~ <7> 13. The gas barrier laminate according to claim 12, <9> the layered inorganic compound contained in the water vapor barrier layer is at least one selected from the group consisting of mica, bentonite, and kaolin; <8> 2. The gas barrier laminate according to claim 1 . <10> the anionic binder is at least one selected from the group consisting of a styrene-butadiene copolymer, a styrene-acrylic copolymer, and an olefin-unsaturated carboxylic acid copolymer; <8> or <9> 2. The gas barrier laminate according to claim 1 . <11> The surface charge of the cationic resin is 0.1 to 10 meq / g. <8> ~ <10> 13. The gas barrier laminate according to claim 12,
[0013] <12> <1> ~ <11> 2. A gas barrier seal paper having a sealant layer on the gas barrier layer in the gas barrier laminate according to any one of claims 1 to 11. <13> The sealant layer is formed by applying a resin to a water-based coating. <12> 2. The gas barrier seal paper according to claim 1 . <14> A packaging material, <1> ~ <11> 13. The gas barrier laminate according to claim 12, <15> A packaging material, <12> or <13> 2. The gas barrier seal paper according to claim 1 . DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The gas barrier laminate of the present embodiment is a gas barrier laminate having a water vapor barrier layer and a gas barrier layer, in this order, on at least one surface of a paper substrate, the gas barrier layer contains a water-suspendable polymer, the wetting tension of the surface of the gas barrier layer measured in accordance with JIS K 6768:1999 is 60 mN / m or more and 70 mN / m or less; The Cobb water absorption of the surface of the gas barrier layer, measured in accordance with JIS P 8140:1998 at a temperature of 23°C and a contact time of 120 seconds, is 2.5 g / m 2 is as follows: When a laminate sheet is formed by laminating a 20 μm-thick non-oriented polypropylene film to the surface of the gas barrier layer of the gas barrier laminate, the oxygen permeability of the laminate sheet measured at a temperature of 23° C. and a relative humidity of 85% in accordance with JIS K 7126-2:2006 is 20 mL / m 2 ·day·atm or less.
[0015] The gas barrier laminate of the present embodiment has good water resistance, water vapor barrier property, and gas barrier property, and can further exhibit sufficient gas barrier property (particularly gas barrier property under a high humidity environment) even after applying a sealant using an aqueous medium (for example, coating of an aqueous heat sealant or lamination of a film). The present inventors speculate that the mechanism by which this effect is exhibited is as follows.
[0016] By setting the wetting tension of the gas barrier layer surface to 60 mN / m or more, the polarity of the gas barrier layer surface is increased. As a result, when a sealant layer is formed on the gas barrier layer using an aqueous medium, the adhesion between the gas barrier layer and the sealant layer is improved. As a result, high gas barrier properties can be maintained even after the sealant is applied. Furthermore, by setting the wetting tension of the gas barrier layer surface to 70 mN / m or less, the difference with the surface tension of the sealant paint is not too large, and the wettability is good. As a result, when a sealant layer is formed on the gas barrier layer using an aqueous medium, the adhesion between the gas barrier layer and the sealant layer is improved. As a result, high gas barrier properties can be maintained even after the sealant is applied.
[0017] In addition, the Cobb water absorption of the gas barrier layer surface at a temperature of 23°C and a contact time of 120 seconds was 2.5 g / m 2By making the film less prone to water permeation, a film with few defects can be formed, which provides high water resistance, water vapor barrier properties, and gas barrier properties. Furthermore, the oxygen permeability at a temperature of 23°C and a relative humidity of 85% can be reduced to 20 mL / m 2 By setting the humidity to 100% by weight per unit area per day atm or less, high gas barrier properties can be exhibited even after application of a sealant using an aqueous medium. It is presumed that due to these synergistic effects, the gas barrier laminate of this embodiment can exhibit sufficient gas barrier properties (particularly gas barrier properties in a high humidity environment) even after application of a sealant using an aqueous medium. Note that the above mechanism is based on presumption, and the mechanism by which the above effect is exhibited is not limited thereto.
[0018] The present embodiment will be described in detail below. The following description of the constituent elements may be based on a representative embodiment or a specific example, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "~" means a range including the numerical values before and after "~" as the lower and upper limits. When a numerical range is described in stages, the upper and lower limits of each numerical range can be combined arbitrarily.
[0019] (Paper support) The paper support used in the gas barrier laminate is not particularly limited as long as it is a commonly used paper containing plant-derived pulp as the main component. Examples of the paper include bleached kraft paper, unbleached kraft paper, wood-free paper, paperboard, liner paper, coated paper, one-sided gloss paper, glassine paper, graphene paper, etc. The paper support is preferably made of paper containing pulp as a main component, which is easily dispersible in water by mechanical disintegration.
[0020] The disintegration freeness (freeness) of the paper support measured according to JIS P8121:2012 is preferably 800 ml or less, more preferably 500 ml or less, from the viewpoint of improving gas barrier properties. Here, disintegration freeness refers to the Canadian standard freeness measured according to JIS P8121:2012 for the pulp obtained by disintegrating the paper after papermaking according to JIS P8220-1:2012. Methods for adjusting disintegration freeness include a method of beating the pulp. Known methods can be used for beating the pulp.
[0021] The basis weight of the paper support is not particularly limited, but is preferably 20 to 400 g / m 2 It is preferable that the thickness is 30 to 320 g / m 2 is more preferred.
[0022] The thickness of the paper support is not particularly limited, but is preferably from 10 to 200 μm, and more preferably from 20 to 100 μm.
[0023] The density of the paper support is not particularly limited, but is preferably 0.30 to 1.50 g / cm 3 and preferably 0.50 to 1.00 g / cm 3 It is more preferable that:
[0024] The Oken smoothness of the surface of the paper support on which the water vapor barrier layer is to be formed is preferably 5 seconds or more, more preferably 10 seconds or more, and even more preferably 15 seconds or more. By making the Oken smoothness of the surface of the paper support on which the water vapor barrier layer is to be formed 5 seconds or more, a smoother water vapor barrier layer is formed, and the water vapor barrier property of the gas barrier laminate is further improved. The upper limit of the Oken smoothness of the surface of the paper support on which the water vapor barrier layer is to be formed is not particularly limited, but is preferably 1000 seconds or less, more preferably 100 seconds or less, and even more preferably 30 seconds or less. Here, the Oken smoothness of the paper support surface is a value measured in accordance with JIS P 8155:2010.
[0025] The sizing degree of the paper support is not particularly limited, but from the viewpoint of improving the barrier property, it is preferable to use a sizing degree according to JIS The Stockigt sizing degree according to P 8122:2004 is preferably 1 second or more. The sizing degree of the paper support can be controlled by the type and content of an internal sizing agent such as a rosin-based, alkyl ketene dimer-based, alkenyl succinic anhydride-based, styrene-acrylic, higher fatty acid-based, or petroleum resin-based agent, the type of pulp, smoothing treatment, etc. The content of the internal sizing agent is not particularly limited, but is preferably 0 to 3 parts by mass relative to 100 parts by mass of pulp in the paper support.
[0026] The paper support may further contain known internal additives, such as fillers such as titanium dioxide, kaolin, talc, and calcium carbonate, paper strength agents, retention aids, pH adjusters, drainage improvers, water resistance agents, softeners, antistatic agents, defoamers, slime control agents, dyes and pigments, etc.
[0027] (Water vapor barrier layer) The water vapor barrier layer is a layer having a function of preventing the transmission of water vapor, and preferably contains a layered inorganic compound, a cationic resin, and an anionic binder.
[0028] <Layered inorganic compounds> The layered inorganic compound has a flat shape. In the water vapor barrier layer, the flat layered inorganic compound is arranged in a laminated state almost parallel to the plane (surface) of the paper support. In this state, the area where the layered inorganic compound is not present is small in the planar direction, so that water vapor permeation is suppressed. In addition, in the thickness direction, the flat layered inorganic compounds are arranged parallel to the plane of the paper support, so that water vapor that has penetrated into the layer passes through while bypassing the layered inorganic compounds, so that water vapor permeation is suppressed. As a result, the water vapor barrier layer can exhibit excellent water vapor barrier properties.
[0029] The average length of the layered inorganic compound is preferably 1 to 100 μm, more preferably 2 to 50 μm, and even more preferably 3 to 20 μm. Here, the average length of the layered inorganic compound refers to the average length of the major axis in the planar direction of the layered inorganic compound. When the average length is 1 μm or more, the layered inorganic compound in the water vapor barrier layer is easily aligned parallel to the paper support. Also, when the average length is 100 μm or less, there is less concern that a part of the layered inorganic compound will protrude from the water vapor barrier layer.
[0030] The aspect ratio of the layered inorganic compound is preferably 200 or more, more preferably 300 or more, and even more preferably 500 or more. Furthermore, from the viewpoint of reducing the coating amount of the water vapor barrier layer and improving the recyclability and lightness of the gas barrier laminate, the aspect ratio of the layered inorganic compound is preferably 200 or more, more preferably 300 or more, even more preferably 500 or more, and particularly preferably 800 or more. The upper limit of the aspect ratio of the layered inorganic compound is not particularly limited, but is preferably 10000 or less, more preferably 5000 or less, and even more preferably 2000 or less. Here, the aspect ratio is a value calculated from a microscopic enlarged photograph of the cross section of the water vapor barrier layer, and is the average value (arithmetic mean value of 20 to 30 samples) of the value obtained by dividing the length of the layered inorganic compound by its thickness. By setting the aspect ratio of the layered inorganic compound within the above range, the water vapor barrier layer can exhibit better water vapor barrier properties. Furthermore, by setting the aspect ratio of the layered inorganic compound within the above range, the amount of the layered inorganic compound added to the water vapor barrier layer can be reduced.
[0031] The thickness of the layered inorganic compound is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. The lower limit of the thickness of the layered inorganic compound is not particularly limited, but is preferably 2 nm or more. Here, the thickness of the layered inorganic compound is the average thickness of the layered inorganic compound measured from a microscopic magnified photograph of the cross section of the water vapor barrier layer (arithmetic mean value of 20 to 30 samples). The thickness is measured in the direction perpendicular to the long axis of the layered inorganic compound.
[0032] By setting the average thickness of the layered inorganic compound within the above range, the number of laminations of the layered inorganic compound in the water vapor barrier layer increases, and the water vapor barrier layer can exhibit higher water vapor barrier properties. In particular, when a layered inorganic compound having a large aspect ratio and a small thickness is used, the water vapor barrier layer forms a dense film without voids. This phenomenon can also be observed from a magnified microscopic photograph of the cross section of the water vapor barrier layer. Such a dense film structure without voids of the water vapor barrier layer forms a tough film and can effectively suppress folding cracks. In addition, it is also possible to suppress the penetration of the coating liquid of the gas barrier layer laminated on the water vapor barrier layer, which contributes to the formation of a uniform gas barrier layer.
[0033] In this embodiment, the aspect ratio of the layered inorganic compound contained in the water vapor barrier layer is 200 or more (preferably 500 or more, more preferably 800 or more), and the thickness is 100 nm or less.
[0034] Specific examples of layered inorganic compounds include micas such as mica and brittle mica, bentonite, kaolinite (kaolin mineral, hereinafter also referred to as "kaolin"), pyrophyllite, talc, smectite, vermiculite, chlorite, septe chlorite, serpentine, and stilpnomelane. , montmorillonite, etc. Among these, from the viewpoint of improving the water vapor barrier property, the layered inorganic compound is preferably at least one selected from the group consisting of mica, bentonite, and kaolin, and more preferably at least one selected from mica and kaolin. Examples of mica include synthetic mica, white mica (muscovite), sericite, phlogopite, black mica (biotite), fluorine phlogopite (artificial mica), red mica, soda mica, vanadium mica, illite, chin mica, paragonite, brittle mica, etc. Among these, swelling mica is preferable as the mica because it has a high aspect ratio. In addition, kaolin may be a natural product or a synthetic product (engineered kaolin). Among these, engineered kaolin is preferable because it has a high aspect ratio. In addition, an example of bentonite is montmorillonite.
[0035] The content of the layered inorganic compound is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 75% by mass or less, even more preferably 70% by mass or less, particularly preferably 30% by mass or less, and especially preferably 20% by mass or less, based on the total solid mass contained in the water vapor barrier layer. On the other hand, the content of the layered inorganic compound is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 5% by mass or more, and particularly preferably 10% by mass or more, based on the total solid mass contained in the water vapor barrier layer. In this embodiment, the content of the layered inorganic compound may be reduced by increasing the aspect ratio of the layered inorganic compound and decreasing the thickness. In addition, by increasing the strength of the water vapor barrier layer, it is possible to suppress the layered inorganic compound from falling off from the water vapor barrier layer.
[0036] The content of the layered inorganic compound is preferably 0.1 to 800 parts by mass, more preferably 1 to 500 parts by mass, even more preferably 2 to 400 parts by mass, even more preferably 5 to 300 parts by mass, particularly preferably 10 to 250 parts by mass, and especially preferably 13 to 30 parts by mass, relative to 100 parts by mass of the anionic binder in the water vapor barrier layer. When the content of the layered inorganic compound is equal to or more than the lower limit, water vapor barrier properties are easily exhibited. In addition, by setting the content of the layered inorganic compound to the upper limit or less, it is possible to suppress a part of the layered inorganic compound from being exposed from the surface of the water vapor barrier layer, thereby increasing the water vapor permeability. In addition, by setting the content of the layered inorganic compound to the upper limit or less, it is possible to improve the coatability of the gas barrier layer laminated on the water vapor barrier layer.
[0037] <Cationic resin> The water vapor barrier layer preferably contains a cationic resin. By adding a cationic resin to the water vapor barrier layer in addition to the layered inorganic compound, the water vapor barrier properties can be significantly improved.
[0038] The reason why the water vapor barrier property is improved by adding a cationic resin is, for example, as follows. It is known that in a layered inorganic compound, the planar portion of the flat plate-like form is easily charged with anionic charge and the edge portion is easily charged with cationic charge, so that the layered inorganic compounds form a so-called house-of-cards structure in which the layered inorganic compounds are agglomerated three-dimensionally with each other. Due to such a house-of-cards structure, the viscosity of the aqueous dispersion of the layered inorganic compound tends to be high. On the other hand, the house-of-cards structure is easily broken when force is applied by stirring or the like, so that the aqueous dispersion of the layered inorganic compound exhibits high thixotropy. When an appropriate cationic resin is added to this, the cationic resin is adsorbed to the anionic planar portion of the layered inorganic compound, thereby destroying the house-of-cards structure. As a result, it is presumed that the layered inorganic compound is inhibited from agglomerating three-dimensionally, and the flat plate-like layered inorganic compound is easily stacked parallel to the plane of the paper support, which leads to an improvement in the water vapor barrier property.
[0039] Specific examples of the cationic resin include polyalkylene polyamines, polyamide compounds, formaldehyde condensation reaction products of polyamidoamine-epihalohydrin or polyamidoamine-epihalohydrin, formaldehyde condensation reaction products of polyamine-epihalohydrin or polyamine-epihalohydrin, formaldehyde condensation reaction products of polyamide polyurea-epihalohydrin or polyamide polyurea-epihalohydrin, polyamine polyurea-epihalohydrin or polyamine polyurea-epihalohydrin, Examples of the polyamide polyurea-epihalohydrin formaldehyde condensation reaction products include polyamide amine polyurea-epihalohydrin or polyamide amine polyurea-epihalohydrin formaldehyde condensation reaction products, polyamide polyurea compounds, polyamine polyurea compounds, polyamide amine polyurea compounds and polyamide amine compounds, polyethyleneimine, polyvinylpyridine, amino-modified acrylamide compounds, polyvinylamine, and polydiallyl dimethyl ammonium chloride.
[0040] Among them, the cationic resin is preferably a polyamide compound, more preferably a modified polyamide resin. The modified polyamide resin may be a commercially available product, such as SPI203(50)H manufactured by Taoka Chemical Co., Ltd.
[0041] The surface charge of the cationic resin is preferably 0.1 to 10 meq / g, more preferably 0.1 to 5.0 meq / g, even more preferably 0.1 to 4.0 meq / g, even more preferably 0.1 to 2.0 meq / g, and particularly preferably 0.2 to 1.0 meq / g. When the surface charge of the cationic resin is within the above numerical range, it becomes easy to destroy the card house structure, and it can coexist appropriately with the anionic binder described later. The surface charge of the cationic resin is measured by the method described below. First, a sample polymer is dissolved in water to obtain a solution with a polymer concentration of 1 ppm. 0.001N sodium polyethylene sulfonate is dropped into the solution using a charge analyzer Mutek PCD-04 type (manufactured by BTG Co., Ltd.) to measure the charge amount.
[0042] The content of the cationic resin may be appropriately selected depending on the type of layered inorganic compound and anionic binder used in the water vapor barrier layer, but from the viewpoint of improving the water vapor barrier property, it is preferably 0.01 to 300 parts by mass, more preferably 0.1 to 250 parts by mass, even more preferably 0.5 to 150 parts by mass, even more preferably 1 to 100 parts by mass, even more preferably 40 to 90 parts by mass, and particularly preferably 1 to 5 parts by mass, relative to 100 parts by mass of the layered inorganic compound. The content of the cationic resin is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 30 parts by mass, even more preferably 1 to 20 parts by mass, and particularly preferably 2 to 15 parts by mass, relative to 100 parts by mass of the anionic binder in the water vapor barrier layer.
[0043] <Anionic binder> The water vapor barrier layer further contains an anionic binder. By containing an anionic binder in the water vapor barrier layer, the water vapor barrier property of the water vapor barrier layer can be more effectively improved. This is thought to be because, as described above, the planar portion of the layered inorganic compound is anionic, but when the cationic resin is adsorbed, the surface becomes cationic, and as a result, the affinity with the anionic binder is enhanced.
[0044] Examples of the anionic binder include binders containing a monomer unit containing an anionic group. Among them, the anionic binder is preferably a binder containing a monomer unit containing a carboxyl group. Examples of the anionic binder include styrene-butadiene copolymers, styrene-acrylic copolymers, methacrylate-butadiene copolymers, acrylonitrile-butadiene copolymers, olefin-unsaturated carboxylic acid copolymers, acrylate-butadiene copolymers, methacrylate-butadiene ... Among these, the anionic binder is preferably at least one selected from the group consisting of styrene-butadiene copolymers, styrene-acrylic copolymers, and olefin-unsaturated carboxylic acid copolymers, and more preferably an olefin-unsaturated carboxylic acid copolymer, because it has good water resistance, good elongation, and is less likely to cause cracks in the coating layer due to folding.
[0045] Styrene-butadiene copolymers are copolymers obtained by emulsion polymerization of aromatic vinyl compounds such as styrene, α-methylstyrene, vinyltoluene, pt-butylstyrene, and chlorostyrene, conjugated diene compounds such as 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene, and other compounds that can be copolymerized with these. Styrene is the preferred aromatic vinyl compound, and 1,3-butadiene is the preferred conjugated diene compound.
[0046] Styrene-acrylic copolymers are copolymers obtained, for example, by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, pt-butylstyrene, and chlorostyrene, acrylic compounds such as acrylic acid, methacrylic acid, (meth)acrylic acid esters, (meth)acrylamidopropanesulfonic acid, and (meth)acrylic acid sulfoalkyl sodium salts (the number of carbon atoms in the alkyl group is 2 to 3), and other compounds copolymerizable with these. Styrene compounds are preferably styrene, and acrylic compounds are preferably acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters, with acrylic acid and acrylic acid esters being more preferable. As (meth)acrylic acid esters, acrylic acid alkyl esters are preferable, and the number of carbon atoms in the alkyl group is preferably 1 to 6.
[0047] Olefin-unsaturated carboxylic acid copolymers are copolymers of olefins, especially α-olefins such as ethylene and propylene, with acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, and methacrylic acid. It is a copolymer obtained by emulsion polymerization of monomers consisting of unsaturated carboxylic acids such as polybutene tricarboxylic acid, fumaric acid, maleic acid, and butene tricarboxylic acid, unsaturated polycarboxylic acid alkyl esters having at least one carboxyl group such as itaconic acid monoethyl ester, fumaric acid monobutyl ester, and maleic acid monobutyl ester, unsaturated sulfonic acid monomers or salts thereof such as acrylamidopropanesulfonic acid, acrylic acid sulfoethyl sodium salt, and methacrylic acid sulfopropyl sodium salt, and other compounds copolymerizable therewith. As the olefin, α-olefins, particularly ethylene, are preferred. As the unsaturated carboxylic acid monomer, unsaturated sulfonic acid monomer or salt thereof, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, etc. are preferable.
[0048] The olefin-unsaturated carboxylic acid copolymer is preferably an ammonium salt of an ethylene-acrylic acid copolymer. For example, an aqueous dispersion of an ammonium salt of an ethylene-acrylic acid copolymer is commercially available as ZAIXXEN (registered trademark) AC (copolymerization ratio of acrylic acid: 21.1% by mass, manufactured by Sumitomo Seika Chemicals Co., Ltd.).
[0049] The above-mentioned anionic binder may further be copolymerized with other copolymerizable compounds, specifically, cyano group-containing ethylenically unsaturated compounds, glycidyl ethers of ethylenically unsaturated acids, glycidyl ethers of unsaturated alcohols, (meth)acrylamide compounds, etc.
[0050] The method for producing the anionic binder is not particularly limited. For example, the anionic binder can be obtained by copolymerizing a monomer containing a carboxy group (e.g., an unsaturated carboxylic acid) and a monomer copolymerizable therewith. Alternatively, for example, a monomer containing a carboxy group is introduced into a polymer. The copolymerization ratio of the monomer containing a carboxy group is preferably 1 to 50 mol %.
[0051] The weight-average molecular weight of the anionic binder is preferably 10,000 to 10 million, more preferably 100,000 to 5 million. By setting the weight-average molecular weight of the anionic binder within the above range, the viscosity of the coating liquid for forming the water vapor barrier layer can be set within an appropriate range. The weight-average molecular weight is a polystyrene-equivalent value measured by gel permeation chromatography.
[0052] The content of the anionic binder is not particularly limited, but is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, even more preferably 25% by mass or more, particularly preferably 30% by mass or more, even more preferably 50% by mass or more, and most preferably 60% by mass or more, relative to the total solid mass contained in the water vapor barrier layer. Also, the content of the anionic binder is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less, relative to the total solid mass contained in the water vapor barrier layer.
[0053] In addition to the layered inorganic compound, the cationic resin, and the anionic binder, the water vapor barrier layer may contain a dispersant, a surfactant, a defoamer, a wetting agent, a dye, a color adjuster, a thickener, etc. The water vapor barrier layer preferably does not contain a metal foil.
[0054] The thickness of the water vapor barrier layer is preferably 1 to 30 μm, more preferably 3 to 20 μm, and even more preferably 4 to 10 μm. The coating amount of the water vapor barrier layer is 1 to 30 g / m2 in terms of solid content. 2 It is preferable that the thickness is 3 to 20 g / m 2 It is more preferable that:
[0055] (Gas barrier layer) The gas barrier layer is a layer having a function of mainly preventing the permeation of oxygen gas. From the viewpoint of achieving the above-mentioned effects, particularly sufficient gas barrier properties even after application of a sealant using an aqueous medium, the gas barrier layer contains a water-suspendable polymer.
[0056] <Water-suspended polymer> The water-suspendable polymer used in this embodiment is a polymer having a solubility of 10 g / L or less in water at 25° C. In this embodiment, the water-suspendable polymer is preferably derived from a polymer (particle) dispersed in an emulsion.
[0057] The water-suspendable polymer is not particularly limited, and examples thereof include urethane resins, vinylidene chloride resins, olefin resins, polyester resins, nylon resins, epoxy resins, melamine resins, polyvinyl alcohol resins, acrylonitrile resins, polycarboxylic acid resins, silicone resins, and the like. The water-suspendable polymer may be used alone or in combination of two or more. Among them, the water-suspendable polymer is preferably at least one selected from the group consisting of urethane resins and vinylidene chloride resins. By forming a gas barrier layer using a urethane resin and / or a vinylidene chloride resin, the wetting tension and Cobb water absorbency of the gas barrier layer surface can be adjusted to a desired range. In addition, by forming a gas barrier layer using a urethane resin and / or a vinylidene chloride resin, excellent gas barrier properties can be exhibited even in a high humidity environment.
[0058] The urethane resin can be produced by a known production method. For example, the urethane resin can be produced by a method comprising the steps of: The polyisocyanate compound can be obtained by reacting with a hydroxy acid (e.g., a dihydroxy acid). It can also be obtained by reacting with a polyol compound (e.g., a polyester polyol, a polyether polyol) and / or a chain extender in addition to the polyisocyanate compound and the polyhydroxy acid.
[0059] The urethane resin preferably contains at least one selected from the group consisting of a structural unit derived from meta-xylylene diisocyanate and a structural unit derived from hydrogenated meta-xylylene diisocyanate. Such a urethane resin exhibits high cohesive strength due to hydrogen bonds and a stacking effect between xylylene groups, so that the gas barrier layer is likely to exhibit excellent gas barrier properties. The structural unit derived from meta-xylylene diisocyanate refers to a monomer unit in the urethane resin that is reacted with meta-xylylene diisocyanate. The same applies to the structural unit derived from hydrogenated meta-xylylene diisocyanate and the structural unit derived from polyisocyanate. The monomer unit refers to a form in which a monomer substance in a polymer is reacted.
[0060] In the urethane resin, the total mol% of the meta-xylylene diisocyanate-derived structural units and the hydrogenated meta-xylylene diisocyanate-derived structural units is preferably 50 mol% or more, more preferably 60 mol% or more, based on the total amount of polyisocyanate-derived structural units in the urethane resin. There is no particular upper limit, but it is preferably 95 mol% or less, more preferably 90 mol% or less. The mol% of the structural units is 1 The identification can be performed using known analytical techniques such as H-NMR.
[0061] The urethane resin may have a hydroxyl group, and the hydroxyl value is preferably 50 mgKOH / g or more, more preferably 100 mgKOH / g or more, and even more preferably 150 mgKOH / g or more. The upper limit of the hydroxyl value is not particularly limited, but is preferably 1000 mgKOH / g or less, more preferably 800 mgKOH / g or less, and even more preferably 600 mgKOH / g or less. When the hydroxyl value of the urethane resin is within the above range, the gas barrier layer is more likely to exhibit oxygen barrier properties. In addition, by setting the hydroxyl value of the urethane resin within the above range, the heat fusion property of the gas barrier layer can be improved, and as a result, the heat sealability of the gas barrier laminate can also be improved. The hydroxyl value is measured in accordance with JIS K0070-1992, and the number of milligrams of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of the sample is acetylated is measured.
[0062] Urethane resin has an oxygen permeability of 100.0 mL / (m2) at 23°C and 50% relative humidity when converted into a 25 μm thick sheet. 2 ·day·atm) or less, and 50.0mL / (m 2 ·day·atm) or less, and 25.0mL / (m 2 ·day·atm) or less, and more preferably 10.0 mL / (m 2 ·day·atm) or less, and even more preferably 3.0 mL / (m 2 It is particularly preferable that the oxygen permeability of the film is 0 mL / (m 2 ·day ·atm) or less when converted into a 25 μm thick sheet at 23°C and a relative humidity of 50%. 2 ·day·atm). The oxygen permeability converted to a 25 μm thick sheet is measured by forming a 25 μm thick sheet using the target urethane resin. In this specification, the oxygen permeability of the sheet is measured using an oxygen permeability measuring device (OX-TRAN2 / 22, manufactured by MOCON) at 23° C. and a relative humidity of 50%.
[0063] The glass transition temperature of the urethane resin is preferably 150° C. or less, more preferably 140° C. or less, and particularly preferably 135° C. or less. The glass transition temperature of the urethane resin is measured in accordance with JIS K 7122:2012.
[0064] As the urethane-based resin, a synthetic product may be used, and examples of the synthetic product include the urethane-based resins described in International Publication No. 2015 / 016069. As the urethane-based resin, a commercially available product may be used, and examples include "Takelac W series (product name)", "Takelac WPB series (product name)", and "Takelac WS series (product name)" manufactured by Mitsui Chemicals, Inc., and specifically, Takelac WPB-341 is exemplified. Other commercially available products include "HPU W-003" (hydroxyl value 235 mg KOH / g) manufactured by Dainichiseika Chemicals Co., Ltd.
[0065] The vinylidene chloride resin can be produced by a known production method. For example, the vinylidene chloride resin can be obtained from a homopolymer of vinylidene chloride (polyvinylidene chloride, PVDC), a copolymer of vinylidene chloride and a monomer copolymerizable with vinylidene chloride, etc. The monomer copolymerizable with vinylidene chloride is not particularly limited, but includes vinyl chloride, (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate, acrylonitrile, isobutylene, and vinyl acetate.
[0066] As the vinylidene chloride resin, commercially available products may be used, such as "Saran Latex L549B" manufactured by Asahi Kasei Corporation and Diofan B204 manufactured by Solvay.
[0067] The weight average molecular weight of the water-suspendable polymer is preferably 1,000 to 20,000,000, and more preferably 5,000 to 5,000,000. The weight average molecular weight is measured by gel permeation chromatography and is expressed in terms of polystyrene.
[0068] The average particle size of the water-suspendable polymer in the emulsion is preferably 0.001 to 100 μm, and more preferably 0.01 to 10 μm. The average particle size can be measured by dynamic light scattering.
[0069] The content of the water-suspendable polymer is preferably 10 to 100 mass %, more preferably 20 to 100 mass %, even more preferably 30 to 95 mass %, even more preferably 40 to 90 mass %, and particularly preferably 60 to 85 mass %, based on the total solid content mass contained in the gas barrier layer. By setting the content of the water-suspendable polymer within the above range, the gas barrier properties of the gas barrier laminate under high humidity conditions can be more effectively improved.
[0070] The content of the water-suspendable polymer in the resin component contained in the gas barrier layer is preferably 50 to 100 mass%, more preferably 80 to 100 mass%, even more preferably 90 to 100 mass%, and even more preferably 95 to 100 mass%.
[0071] As described above, the water-suspendable polymer is preferably derived from a polymer (particle) dispersed in an emulsion. In other words, the gas barrier layer is preferably a layer formed by applying an emulsion coating liquid onto a paper support. In this specification, the gas barrier layer thus formed is sometimes referred to as an emulsion coating layer. In this embodiment, from the viewpoint of further improving the gas barrier properties, it is particularly preferable that the gas barrier layer is at least one coating layer selected from a urethane-based resin emulsion (also referred to as a "urethane-based emulsion" in this specification) and a vinylidene chloride-based resin emulsion (also referred to as a "vinylidene chloride-based emulsion" in this specification). In addition, the urethane-based emulsion is preferably at least one coating layer selected from a vinylidene chloride-based resin emulsion (also referred to as a "vinylidene chloride emulsion" in this specification). As the emulsion, a commercially available product may be used. For example, Takelac WPB-341 manufactured by Mitsui Chemicals, Inc. may be mentioned. As the vinylidene chloride-based emulsion, a commercially available product may be used. For example, Saran Latex L549B manufactured by Asahi Kasei Corporation may be mentioned.
[0072] In addition to the water-suspendable polymer, the gas barrier layer preferably contains a layered inorganic compound. That is, the gas barrier layer preferably contains a water-suspendable polymer and a layered inorganic compound. By containing a layered inorganic compound in the gas barrier layer, the gas barrier property can be further improved (oxygen permeability can be further reduced). Examples of the layered inorganic compound include the layered inorganic compounds that can be contained in the water vapor barrier layer as described above, and one type may be used alone, or two or more types may be used in combination.
[0073] The preferred ranges of the average length, aspect ratio and thickness of the layered inorganic compound are the same as those described in the above <Layered inorganic compound>. In particular, the aspect ratio of the layered inorganic compound contained in the gas barrier layer is preferably 200 or more (preferably 300 or more, more preferably 500 or more) and the thickness is preferably 100 nm or less. By containing a layered inorganic compound having the above aspect ratio and thickness, the gas barrier property of the gas barrier laminate (particularly under high humidity conditions) can be more effectively improved.
[0074] Specific examples of the layered inorganic compound contained in the gas barrier layer are the same as those described in the above section of <Layered inorganic compound>. Among them, at least one selected from the group consisting of mica, bentonite and kaolin is preferable, and at least one selected from mica and kaolin is more preferable. By containing the layered inorganic compound as described above in the gas barrier layer, the gas barrier property of the gas barrier laminate under high humidity conditions can be more effectively improved. The layered inorganic compound contained in the gas barrier layer may be the same type as the layered inorganic compound contained in the water vapor barrier layer, or may be different from the layered inorganic compound contained in the water vapor barrier layer.
[0075] From the viewpoint of reducing the oxygen transmission rate ratio (humidity dependency of oxygen transmission rate) of the gas barrier laminate, the gas barrier layer preferably contains two or more kinds of layered inorganic compounds having different aspect ratios. Specifically, the gas barrier layer preferably contains a layered inorganic compound (layered inorganic compound A) having an aspect ratio of less than 500 and a layered inorganic compound (layered inorganic compound B) having an aspect ratio of 500 or more.
[0076] The aspect ratio of the layered inorganic compound A is more preferably 10 to 300, further preferably 20 to 200, and further more preferably 25 to 50. The aspect ratio of the layered inorganic compound B is more preferably 600 to 5000, further preferably 750 to 2500, and further more preferably 800 to 1200. The layered inorganic compound A may be used alone or in combination of two or more kinds. The layered inorganic compound B may be used alone or in combination of two or more kinds.
[0077] The average length of the layered inorganic compound A is more preferably 0.2 to 5 μm, and even more preferably 0.5 to 2 μm. The thickness of the layered inorganic compound A is more preferably 10 nm to 500 nm, and even more preferably 20 nm to 100 nm. The average length of the layered inorganic compound B is more preferably 2 to 50 μm, and even more preferably 3 to 20 μm. The thickness of the layered inorganic compound B is more preferably 2 nm to 50 nm, and even more preferably 3 nm to 8 nm.
[0078] The layered inorganic compounds A and B are preferably at least one selected from the group consisting of mica, bentonite and kaolin, and at least one selected from mica and kaolin. It is more preferable that the layered inorganic compound A is kaolin and the layered inorganic compound B is mica.
[0079] When the layered inorganic compound is contained in the gas barrier layer, the content of the layered inorganic compound is not particularly limited, but is preferably 0.5 to 500 parts by mass, more preferably 1 to 300 parts by mass, even more preferably 2 to 200 parts by mass, even more preferably 5 to 150 parts by mass, and particularly preferably 10 to 70 parts by mass, relative to 100 parts by mass of the water-suspendable polymer in the gas barrier layer. By setting the content of the layered inorganic compound within the above range, the gas barrier property of the gas barrier laminate under high humidity conditions can be more effectively improved.
[0080] When layered inorganic compounds A and B are used in combination, the content of layered inorganic compound A is preferably 5 to 60 parts by mass, more preferably 15 to 40 parts by mass, relative to 100 parts by mass of the water-suspendable polymer. The content of layered inorganic compound B is preferably 5 to 50 parts by mass, more preferably 10 to 30 parts by mass, relative to 100 parts by mass of the water-suspendable polymer.
[0081] The gas barrier layer may contain, in addition to the water-suspendable polymer and the layered inorganic compound, a pigment, a dispersant, a surfactant, a defoamer, a wetting agent, a dye, a color adjuster, a thickener, etc. The gas barrier layer preferably does not contain a water-soluble polymer such as polyvinyl alcohol. A water-soluble polymer is a polymer whose solubility in water at 25°C exceeds 10 g / L. In addition, the gas barrier layer preferably does not contain a metal foil.
[0082] The thickness of the gas barrier layer is preferably 0.1 to 10 μm, more preferably 0.5 to 5 μm, and further preferably 1 to 3 μm. The coating amount of the gas barrier layer is 0.1 to 10 g / m2 in terms of solid content. 2 It is preferable that the thickness is 0.5 to 5 g / m 2 It is more preferable that:
[0083] <Physical properties of gas barrier laminate> (Wetting tension) The gas barrier laminate has a gas barrier layer surface wetting tension of 60 mN / m or more, preferably 63 mN / m or more, measured in accordance with JIS K 6768:1999. By making the gas barrier layer surface wetting tension equal to or more than the lower limit, the polarity of the gas barrier layer surface is increased. This improves the adhesion between the gas barrier layer and a sealant layer formed on the gas barrier layer using an aqueous medium. Therefore, high gas barrier properties can be maintained even after applying a sealant using an aqueous medium.
[0084] Furthermore, the wetting tension of the gas barrier layer surface is 70 mN / m or less, preferably 65 mN / m or less. By setting the wetting tension of the gas barrier layer surface to the above upper limit or less, the difference with the surface tension of the sealant paint is not too large, and the wettability is good. This improves the adhesion between the gas barrier layer and the sealant layer when a sealant layer is formed on the gas barrier layer using an aqueous medium. This allows high gas barrier properties to be maintained even after the application of a sealant using an aqueous medium.
[0085] The wetting tension can be adjusted to within the above range by adjusting the components used in the gas barrier layer. For example, the wetting tension can be increased by including a layered inorganic compound in the gas barrier layer or by adding a surfactant. On the other hand, the wetting tension can be decreased by adding an antifoaming agent.
[0086] (Cobb absorbency) The Cobb water absorption of the gas barrier layer surface of the gas barrier laminate, measured in accordance with JIS P 8140:1998 at a temperature of 23°C and a contact time of 120 seconds, is 2.5 g / m 2 or less, preferably 1.5 g / m 2 More preferably, it is 1.0 g / m or less. 2 By setting the Cobb water absorbency of the gas barrier layer surface within the above range, a water-impermeable film with few defects can be formed, and high water resistance, water vapor barrier property, and gas barrier property can be obtained. The lower limit of the Cobb water absorbency of the gas barrier layer surface is not particularly limited, but is preferably 0 g / m 2 More than 0.1g / m2 More than 0.2g / m 2 That's all.
[0087] The Cobb water absorbency of the surface of the gas barrier layer can be adjusted to within the above range by adjusting the components and coating amount of the gas barrier layer. For example, the Cobb water absorbency can be reduced by adopting a water-suspendable polymer containing a thermoplastic resin. In addition, if a water-soluble polymer such as polyvinyl alcohol is adopted as the resin component of the gas barrier layer, it is difficult to satisfy the above cup water absorbency.
[0088] (Oxygen permeability) When a laminate sheet is formed by laminating a 20 μm thick non-oriented polypropylene film (CPP film) to the surface of the gas barrier layer of the gas barrier laminate, The oxygen permeability of the laminated sheet at a temperature of 23°C and a relative humidity of 85%, as measured in accordance with ISO 2014-2:2006, is 20 mL / m 2 ·day·atm or less, preferably 15mL / m 2 ·day·atm or less, and more preferably 10mL / m 2 ·day·atm or less, and more preferably 5mL / m 2 ·day·atm or less, and even more preferably 3mL / m 2 Within the above range, sufficient gas barrier properties are maintained even after application of a sealant using an aqueous medium. The lower limit of the oxygen permeability of the laminate sheet is not particularly limited, but is preferably 0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or more, 0.5mL / m 2 The oxygen permeability of the laminated sheet can be reduced by, for example, making the gas barrier layer contain a layered inorganic compound or by making the gas barrier layer thicker.
[0089] (Water vapor permeability) The water vapor permeability of the gas barrier laminate is 50 g / m 2·day or less, and 40g / m 2 ·day or less is more preferable, and 30 g / m 2 25 g / m 2 It is even more preferable that the g / m 2 1 day or less. There is no particular lower limit, but it is preferably 0 g / m 2 ·day or more, 1g / m 2 ·day or more.
[0090] If the water vapor permeability of the gas barrier laminate is within the above range, it can be said that the water vapor permeability of the gas barrier laminate is sufficiently suppressed. Here, the water vapor permeability of the gas barrier laminate is a value measured in accordance with JIS-Z-0208:1976 (cup method) Method B (40°C ± 0.5°C, relative humidity 90% ± 2%). When measuring, the gas barrier layer is placed on the inside.
[0091] The thickness of the gas barrier laminate is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. The thickness of the gas barrier laminate is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, and even more preferably 100 μm or less.
[0092] (Method of manufacturing gas barrier laminate) The method for producing the gas barrier laminate is not particularly limited, and any known method can be used. The gas barrier laminate can be produced by first coating a coating liquid for forming a water vapor barrier layer onto a paper support to form a water vapor barrier layer, and then coating a coating liquid for forming a gas barrier layer to form a gas barrier layer. That is, the method for producing a gas barrier laminate preferably includes a step of coating a coating liquid for forming a water vapor barrier layer onto a paper support to form a water vapor barrier layer, and a step of coating a coating liquid for forming a gas barrier layer onto the water vapor barrier layer to form a gas barrier layer. Each layer may be formed by successively coating and drying the coating liquid, or may be simultaneously coated in multiple layers and then dried.
[0093] In the step of forming the water vapor barrier layer, a coating liquid for forming the water vapor barrier layer is applied onto the paper support. The coating liquid for forming the water vapor barrier layer preferably contains a layered inorganic compound, a cationic resin, and an anionic binder. The coating liquid for forming the water vapor barrier layer also contains a solvent, and the solvent may be water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, or toluene.
[0094] Known coating equipment can be used for coating the water vapor barrier layer-forming coating liquid on the paper support. Examples of coating equipment include a blade coater, a bar coater, an air knife coater, a slit die coater, a gravure coater, a microgravure coater, and a gate roll coater. In particular, for forming the water vapor barrier layer, a coater that scrapes the coating surface, such as a blade coater, a bar coater, an air knife coater, or a slit die coater, is preferred in that it promotes the orientation of the layered inorganic compound.
[0095] In the step of forming the gas barrier layer, it is preferable to coat an emulsion containing a water-suspendable polymer onto the water vapor barrier layer. In particular, it is preferable that the step of forming the gas barrier layer is a step of coating at least one selected from a urethane-based emulsion and a vinylidene chloride-based emulsion. Note that, when the gas barrier layer contains a layered inorganic compound or the like in addition to the water-suspendable polymer, it is preferable to coat a coating liquid in which the layered inorganic compound or the like is dispersed in an emulsion.
[0096] Examples of coating equipment for applying the gas barrier layer coating liquid onto the water vapor barrier layer include the same equipment as described above.
[0097] The drying equipment for drying each coating layer is not particularly limited, and known equipment can be used, such as a hot air dryer, an infrared dryer, a gas burner, and a hot plate.
[0098] In the method for producing a gas barrier laminate, when the coating liquid for forming a water vapor barrier layer contains a layered inorganic compound, a cationic resin, and an anionic binder, the layered inorganic compound in the water vapor barrier layer does not form a card house structure, but is laminated in a uniformly dispersed state. Therefore, the water vapor barrier layer formed has excellent water vapor barrier properties. Furthermore, in the step of forming the water vapor barrier layer, the surface of the water vapor barrier layer is formed smoothly, so that the gas barrier layer thereon can also be formed uniformly. This results in the formation of a gas barrier laminate with even better gas barrier properties.
[0099] <Gas barrier seal paper> The present disclosure also provides a gas barrier seal paper having a sealant layer on the gas barrier layer of the above-mentioned gas barrier laminate.
[0100] The sealant layer is preferably a layer that exhibits adhesiveness when melted by heating or ultrasonic waves, and thus, for example, the sealant layer can bond gas barrier laminates to each other by heat sealing or the like.
[0101] As described above, the gas barrier laminate can have a sealant applied to the gas barrier layer using an aqueous medium. Therefore, in the gas barrier seal paper of this embodiment, the sealant layer may be formed by applying a resin with an aqueous medium. Alternatively, the sealant layer may be formed by laminating a resin using a melt extrusion lamination method or a dry lamination method.
[0102] In the water-based coating, a coating liquid obtained by dissolving or dispersing any resin in a solvent containing water may be used. The method for producing a gas barrier seal paper preferably includes a step of obtaining a gas barrier laminate having a water vapor barrier layer and a gas barrier layer in this order on at least one side of a paper substrate, and a step of applying a sealant layer forming coating liquid on the gas barrier layer of the gas barrier laminate and drying to form a sealant layer, the sealant layer forming coating liquid containing at least water and a resin for forming a sealant layer. The sealant layer forming coating liquid may contain an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, or toluene in addition to water. The sealant layer forming coating liquid may also contain additives such as surfactants that are commonly used in water-based coating.
[0103] Resins used in the sealant layer include acrylic resins such as polyethylene, polypropylene, ethylene-vinyl acetate polymers, ethylene-(meth)acrylic acid copolymers, and styrene-(meth)acrylic acid copolymers; polyester resins; polyvinyl acetate polymers; biodegradable resins, etc. Specific examples of biodegradable resins are not particularly limited, and include, for example, polylactic acid (PLA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), and 3-hydroxybutanoic acid-3-hydroxyhexanoic acid copolymer (PHBH).
[0104] The thickness of the sealant layer is preferably 1 to 50 μm, and more preferably 3 to 30 μm. The amount of the sealant layer formed is 1 to 50 g / m2 in terms of solid content. 2 It is preferable that the thickness is 3 to 30 g / m 2It is more preferable that: The gas barrier seal paper preferably has an oxygen permeability of 3.0 mL / m at a temperature of 23°C and a relative humidity of 85%. 2 ·day·atm or less, preferably 2.5mL / m 2 ·day·atm or less, more preferably 2.0mL / m 2 ·day·atm or less, and even more preferably 1.5mL / m 2 Within the above range, the material can be suitably used as a packaging material (particularly, a packaging material for transported items exposed to high humidity conditions). The oxygen permeability of the gas barrier seal paper is a value measured by the method described in the Examples.
[0105] (Application) The gas barrier laminate and the gas barrier seal paper can be suitably used as packaging materials for food, medical products, electronic components, etc. In particular, the gas barrier laminate and the gas barrier seal paper of the present embodiment have excellent gas barrier properties under high humidity conditions, and therefore can be suitably used as packaging materials for food, medical products, electronic components, etc. that are exposed to high humidity conditions. In addition, since the humidity dependency of oxygen transmission rate is suppressed to a small value in the gas barrier laminate, the gas barrier properties of the gas barrier laminate can be maintained without fluctuation even if temperature or humidity changes occur during transportation or storage, for example. EXAMPLES
[0106] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. In the following formulations, parts are by weight unless otherwise specified.
[0107] <Example 1> To 30.0 parts of an aqueous dispersion of a layered inorganic compound (swellable mica, average length 6.3 μm, aspect ratio approximately 1000, thickness approximately 5 nm, solid content concentration 6 mass%, product name: NTO-05, manufactured by Topy Industries), 34.2 parts of a self-emulsifying emulsion of an ethylene-acrylic acid copolymer (solid content concentration 29.2 mass%, product name: Zaixen AC, manufactured by Sumitomo Seika Chemicals) was added while stirring, and the mixture was stirred. To this, 2.55 parts of a modified polyamide resin (surface charge 0.4 meq / g, solid content concentration 53 mass%, product name: SPI203 (50) H, manufactured by Taoka Chemical Industries) was added and stirred. Furthermore, 0.30 parts of a 25 mass% aqueous ammonia solution was added and stirred. Furthermore, dilution water was added to make the solid content concentration 19 mass%, and the coating material for the water vapor barrier layer was prepared.
[0108] A water dispersion of a layered inorganic compound (swellable mica, average length 6.3 μm, aspect ratio approximately 1000, thickness approximately 5 nm, solid content concentration 6 mass%, product name: NTO-05, manufactured by Topy Industries) was mixed with a polyurethane emulsion A (solid content concentration 30 mass%, glass transition temperature 130°C, oxygen permeability when formed into a 25 μm thick sheet was 2.0 mL / (m 2 100 ml of 10 ...
[0109] The obtained water vapor barrier layer paint was applied to a coating amount of 5.0 g / m 2 To achieve this, one-sided glazed bleached kraft paper (manufactured by Oji F-Tex Co., Ltd., basis weight 50 g / m 2 , thickness 60μm, density 0.83g / cm 3 The water vapor barrier layer paint was then applied to the bleached kraft paper (one side had an Oken smoothness of 16 seconds, the other side had an Oken smoothness of 430 seconds) using a Mayer bar. The bleached kraft paper coated with the water vapor barrier layer paint was then dried at 120°C for 1 minute in a hot air dryer. Furthermore, a gas barrier layer paint was applied to the top of the water vapor barrier layer with a coating weight of 2.0 g / m 2After coating with a Mayer bar so that the coating was performed, the coating was dried in a hot air dryer at 120°C for 1 minute to obtain a gas barrier laminate having a thickness of 65 μm. The water vapor barrier layer had a thickness of 5 μm, and the gas barrier layer had a thickness of 2 μm.
[0110] Regarding the urethane resin in the above urethane emulsion A, 1 When H-NMR measurement was performed, the content of meta-xylylene diisocyanate-derived structural units relative to the total amount of polyisocyanate-derived structural units was 85 mol %. In addition, the solubility of the urethane resin in water at 25°C was 10 g / L or less.
[0111] <Example 2> Urethane emulsion A (solid concentration 30% by mass, glass transition temperature 130°C, oxygen permeability when formed into a 25 μm thick sheet is 2.0 mL / (m 2 33.3 parts of water dispersion of a first layered inorganic compound (swellable mica, average length 6.3 μm, aspect ratio about 1000, thickness about 5 nm, solid content concentration 6 mass%, product name: NTO-05, manufactured by Topy Industries) was added to 33.4 parts of water dispersion of a first layered inorganic compound (engineered kaolin, average length 0.89 μm, aspect ratio about 33, thickness about 30 nm, solid content concentration 50 mass%, product name: Contour Extreme, manufactured by Imerys) and stirred. Further, dilution water was added to make the solid content concentration 10 mass%, and this was used as a paint for the gas barrier layer. A gas barrier laminate having a thickness of 65 μm was obtained in the same manner as in Example 1, except that this paint for the gas barrier layer was used. The thickness of the gas barrier layer was 2 μm.
[0112] <Example 3> Aqueous dispersion B of polyurethane resin binder having hydroxyl groups (manufactured by Dainichi Seikagaku Co., Ltd., HPU W-003, hydroxyl value 235 mg KOH / g, solid content concentration 30%, glass transition temperature ℃) 33.3 parts of the aqueous dispersion of the first layered inorganic compound (swellable mica, average length 6.3 μm, aspect ratio about 1000, thickness about 5 nm, solid content concentration 6 mass%, product name: NTO-05, manufactured by Topy Industries) was added. To this, 6 parts of the aqueous dispersion of the second layered inorganic compound (engineered kaolin, average length 0.89 μm, aspect ratio about 33, thickness about 30 nm, solid content concentration 50 mass%, product name: Contour Extreme, manufactured by Imerys) was added and stirred. Further, dilution water was added to make the solid content concentration 10 mass%, and it was used as the paint of the gas barrier layer. A gas barrier laminate having a thickness of 65 μm was obtained in the same manner as in Example 1 except that this paint of the gas barrier layer was used. In addition, the thickness of the gas barrier layer was 2 μm. The solubility of the polyurethane resin binder in water at 25° C. was 10 g / L or less.
[0113] <Example 4> A gas barrier laminate was obtained in the same manner as in Example 1, except that in the preparation of the coating material for the water vapor barrier layer, 0.4 parts of polyamide-epichlorohydrin resin (surface charge 3.4 meq / g, solid concentration 25 mass%, product name: WS4027, manufactured by Seiko PMC Corporation) was added instead of 2.55 parts of modified polyamide resin (surface charge 0.4 meq / g, solid concentration 53 mass%, product name: SPI203(50)H, manufactured by Taoka Chemical Co., Ltd.).
[0114] <Example 5> A gas barrier laminate was obtained in the same manner as in Example 1, except that a polyvinylidene chloride PVDC emulsion (solid content concentration 51%, Diofan B204, manufactured by Solvay) was used as the coating material for the gas barrier layer, with dilution water added to make the solid content concentration 20 mass%, instead of the mixture of the layered inorganic compound and the urethane emulsion A. The solubility of the PVDC in water at 25°C was 10 g / L or less.
[0115] <Comparative Example 1> An aqueous solution of ethylene-modified polyvinyl alcohol (fully saponified, product name: EXEVAL AQ-4104, manufactured by Kuraray) with a solid content concentration of 15% by mass was prepared, and dilution water was added to this to make the solid content concentration 10% by mass, to prepare a coating material for the gas barrier layer. A gas barrier laminate with a thickness of 65 μm was obtained in the same manner as in Example 1, except that the gas barrier layer was made as described above. The thickness of the gas barrier layer was 2 μm.
[0116] <Comparative Example 2> 100 parts of an aqueous solution of ethylene-modified polyvinyl alcohol (fully saponified, product name: EXEVAL AQ-4104, manufactured by Kuraray) with a solid content concentration of 15% by mass was added with 50 parts of an aqueous dispersion of a layered inorganic compound (swellable mica, average length 6.3 μm, aspect ratio about 1000, thickness about 5 nm, solid content concentration 6% by mass, product name: NTO-05, manufactured by Topy Industries), and further diluted with water to make the solid content concentration 10% by mass, to obtain a coating material for the gas barrier layer. A gas barrier laminate with a thickness of 65 μm was obtained in the same manner as in Example 1, except that the gas barrier layer was the above-mentioned. The thickness of the gas barrier layer was 2 μm.
[0117] <Comparative Example 3> A gas barrier laminate having a thickness of 65 μm was obtained in the same manner as in Example 1, except that an aqueous dispersion of a layered inorganic compound (swellable mica, average length 6.3 μm, aspect ratio approximately 1000, thickness approximately 5 nm, solid content concentration 6 mass%, product name: NTO-05, manufactured by Topy Industries) was not added to the coating material for the gas barrier layer. The thickness of the gas barrier layer was 2 μm.
[0118] <Evaluation of Gas Barrier Laminate> The gas barrier laminates obtained in the examples and comparative examples were evaluated as follows.
[0119] [Wetting tension] The wetting tension of the surface of the gas barrier layer was measured using a wetting reagent (mixture for wetting tension test, manufactured by Kanto Chemical Co., Ltd.) in accordance with JIS K 6768:1999.
[0120] [Cobb Water Absorbency] The test was carried out in accordance with JIS P 8140: 1998. The temperature of the water (distilled water was used) to be brought into contact with the surface of the gas barrier layer of the gas barrier laminate was 23° C., and the contact time was 120 seconds.
[0121] [Oxygen permeability] The oxygen permeability of the gas barrier laminate was measured using an oxygen permeability measuring device (OX-TRAN2 / 22, manufactured by MOCON) under conditions of a temperature of 23°C and a relative humidity of 85%. Specifically, an isocyanate-based adhesive (manufactured by DIC Corporation, a mixture of 10 parts of DIC Dry LX-500 and 1 part of DIC Dry KW-75) was applied at 5 g / m2 to the surface of the gas barrier layer of the gas barrier laminate obtained in the examples and comparative examples. 2 After coating, a 20 μm thick CPP film (GP-32, manufactured by Hokuetsu Chemical Industry Co., Ltd.) was laminated to form a laminate sheet. The laminate sheet was then stored at a temperature of 23° C. and a relative humidity of 85% in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the better the oxygen barrier property.
[0122] [Water vapor permeability] The water vapor permeability of the gas barrier laminates obtained in the examples and comparative examples was measured in accordance with JIS-Z-0208:1976 (cup method) Method B (40°C±0.5°C, relative humidity 90%±2%) with the gas barrier layer facing inward.
[0123] [Suitable for barrier packaging materials] The gas barrier laminates of the Examples and Comparative Examples were evaluated for suitability as a barrier packaging material based on the oxygen permeability and water vapor permeability measured above. 〇: Oxygen permeability is 20mL / m 2 ·day·atm or less, and the water vapor permeability is 5g / m 2 ·day or less ×: Oxygen permeability is 20mL / m 2 ·day·atm or water vapor permeability is 5g / m 2 Greater than day.
[0124] [Processability (gas barrier properties after applying sealant)] For the gas barrier laminates of the Examples and Comparative Examples, a water-based heat seal agent (Michaelman, MFHS1279, ethylene-acrylic acid copolymer, solid content concentration 42%) was diluted with water to 20 mass %, and 5 g / m of solid content was applied onto the gas barrier layer. 2 Mayer The resulting sealant layer was coated with an isocyanate adhesive (a mixture of 10 parts of DIC Dry LX-500 and 1 part of DIC Dry KW-75, manufactured by DIC Corporation) at a rate of 5 g / m 2 After coating, a 20 μm thick CPP film (GP-32, manufactured by Hokuetsu Chemical Industry Co., Ltd.) was laminated to form a laminate sheet. Based on the above, the oxygen permeability was measured at a temperature of 23°C and a relative humidity of 85%. Processing suitability was evaluated based on the measured oxygen permeability. 〇: Oxygen permeability is 20mL / m 2 ·day · atm or less. ×: Oxygen permeability is 20mL / m 2 ·day·larger than atm.
[0125] [Table 1]
[0126] The gas barrier laminates of Examples 1 to 5 had excellent gas barrier properties (gas barrier properties in a high humidity environment) even after application of a sealant using an aqueous medium, compared to the gas barrier laminates of Comparative Examples 1 to 3.
Claims
1. A gas barrier laminate having a water vapor barrier layer and a gas barrier layer in this order on at least one surface of a paper substrate, the gas barrier layer contains a water-suspendable polymer, the gas barrier layer contains a urethane-based resin as the water-suspendable polymer and a layered inorganic compound, or the gas barrier layer contains a vinylidene chloride-based resin as the water-suspendable polymer, the water vapor barrier layer comprises a layered inorganic compound, a cationic resin, and an anionic binder; the surface charge of the cationic resin is 0.1 to 10 meq / g; the wetting tension of the surface of the gas barrier layer measured in accordance with JIS K 6768:1999 is 60 mN / m or more and 70 mN / m or less; The Cobb water absorption of the surface of the gas barrier layer, measured in accordance with JIS P 8140:1998 at a temperature of 23°C and a contact time of 120 seconds, is 2.5 g / m 2 is as follows: When a laminate sheet is formed by laminating a 20 μm-thick non-oriented polypropylene film to the surface of the gas barrier layer of the gas barrier laminate, the oxygen permeability of the laminate sheet measured at a temperature of 23° C. and a relative humidity of 85% in accordance with JIS K 7126-2:2006 is 20 mL / m 2 .day.atm or less.
2. The gas barrier laminate described in claim 1, wherein the cationic resin contains a polyamide compound.
3. The urethane resin has an oxygen permeability of 100.0 mL / m at 23° C. and 50% RH when converted into a sheet having a thickness of 25 μm. 2 3. The gas barrier laminate according to claim 1, wherein the gas barrier density is 1.0×day·atm or less.
4. The gas barrier laminate according to any one of claims 1 to 3, wherein the gas barrier layer comprises a layered inorganic compound.
5. 5. The gas barrier laminate according to claim 4, wherein the layered inorganic compound contained in the gas barrier layer has an aspect ratio of 200 or more and a thickness of 100 nm or less.
6. 6. The gas barrier laminate according to claim 4, wherein the layered inorganic compound contained in the gas barrier layer is at least one selected from the group consisting of mica, bentonite, and kaolin.
7. the layered inorganic compound contained in the gas barrier layer is a layered inorganic compound B having an aspect ratio of 500 or more, 7. The gas barrier laminate according to claim 4, wherein the gas barrier layer further comprises a layered inorganic compound A having an aspect ratio of less than 500.
8. 8. The gas barrier laminate according to claim 1, wherein the layered inorganic compound contained in the water vapor barrier layer is at least one selected from the group consisting of mica, bentonite, and kaolin.
9. The gas barrier laminate according to any one of claims 1 to 8, wherein the anionic binder is at least one selected from the group consisting of a styrene-butadiene copolymer, a styrene-acrylic copolymer, and an olefin-unsaturated carboxylic acid copolymer.
10. 10. A gas barrier seal paper comprising the gas barrier laminate according to claim 1, and a sealant layer on the gas barrier layer.
11. The gas barrier seal paper according to claim 10, wherein the sealant layer is formed by applying a resin by aqueous coating.
12. The gas barrier laminate according to any one of claims 1 to 9, which is a packaging material.
13. The gas barrier seal paper according to claim 10 or 11, which is a packaging material.
Citation Information
Patent Citations
Gas barrier paper and package using the same
JP2013079469A
Paper-made material having gas barrier properties
JP2013079470A
Barrier material made of paper
JP2018058360A
Barrier paper packaging material
WO2013069788A1
Paper-made barrier material
WO2017170462A1